Pengujian Model Kontijensi Akuntansi Manajemen Stratejik terhadap Kinerja UKM di Maluku - Monika Handojono; Victor Cornelis (JRAK: Journal of Accounting Research and Computerized Accounting, 2021)
The sustainability of SMEs is supported by various important factors, both financial and non-financial. This study examines non-financial factors, namely the management accounting adoption model on the performance of SMEs in Maluku. The sample of this study consisted of 63 UKM units located in Ambon City, SBB Regency and Central Maluku Regency. The testing of management accounting adoption contingency models is carried out using path analysis. The result showed that management accounting adoption is a mediator of the relationship between the level of innovation and technology adoption in manufacturing activities with the performance of SMEs. However, this study has not succeeded in proving the relationship between manager characteristics and managers' perceptions of environmental uncertainty with the decision to adopt strategic management accounting by business units. These results indicate that there is a need for further introduction to the benefits of a strategic management accounting system as an important instrument in streamlining the business value chain.